Protección de Celdas Fotovoltaicas Mediante Fusibles Clase gPV - Gómez, Juan Carlos (2013)
During the last 50 years, the application of Photovoltaic cells (PV cells) has increased at a high speed. PV cells have special characteristics that require protective devices specifically designed for this application, among which the fuse presents optimum features. The main characteristics are: dc power generation, low short-circuit current and low X/R ratios, behavior influenced by temperature, etc. The most used gPV fuse specification is the new IEC 60269-6, that gives some rough guidelines. Also fuse manufacturers give “application rules” that have some inconsistencies and difficult the fuse selection. The need for more coordinated work between PV cells and fuses manufacturers is stressed, indicating the areas where this work is required.